DIGITALIZATION AS A FACTOR OF ECONOMIC DEVELOPMENT OF REGIONS IN UZBEKISTAN: CURRENT STATE AND TRENDS - Qurbonova , Malika Ahmad qizi (THE INNOVATION ECONOMY, 2026)
This article analyzes the current processes of digitalization and their impact on the economic development of regions in Uzbekistan. It examines the key directions of digital technology implementation, including infrastructure development, e-government, and digital services expansion. Special attention is given to existing regional disparities, as well as the identification of major trends and challenges in the process of digital transformation. Based on the analysis, recommendations and directions for further improvement of the digital economy at the regional level are proposed.